Women, War and Nationhood in Present Day Croatia, 8.-10.06.1992., First International Conference on the Ethnic Studies Network: Conflict and Change, University of Ulster/ United Nations University, Northern Ireland - Gjurgjan, Ljiljana Ina (1992)
The lecture has addressed the question of both the symbolic and the real role of women in the articulation of national identity. It ahs also looked in the hierarchy of the solidarity in relation to the gender and to the national affiliations.
Neobjavljeno predavanje.
ENG